Metaphysics : the fundamentals - Koons, Robert C.; Pickavance, Timothy H. (Fundamentals of philosophy (Blackwell Publishing Ltd.), 2015)
"The book covers a broad range of key topics, including theories of properties and particulars, the notion of truth-makers, powers and possibilities, material composition, and a variety of issues related to time and causation"--